Home » Aptitude » Algebra » Question
  1. If (a + b – 6)2 + a2 + b2 + 1 + 2b = 2ab + 2a, then the value of a is
    1. 7
    2. 6
    3. 3.5
    4. 2.5
Correct Option: C

(a + b – 6)2 + a2 + b2 + 1 + 2b = 2ab + 2a
⇒  (a + b – 6)2 + a2 + b2 +1 + 2b – 2ab – 2a = 0
⇒  (a + b – 6)2 + (a)2 + (–b)2 + (–1)2 + 2a (–b) + 2 (–b) (–1) + 2 (a) (–1) = 0
⇒  (a + b – 6)2 + (a – b – 1)2 = 0
⇒  a + b – 6 = 0 and a – b – 1 = 0
⇒  a + b = 6 and a – b = 1
On adding these two equations,
a + b + a – b = 6 + 1
⇒  2a = 7

⇒  a =
7
= 3.5
2



Your comments will be displayed only after manual approval.